Antibacterial and Antibiofilm Activity of Daemonorops draco Resin - Wulan Tri Wahyuni; Sri Purwanti; Irmanida Batubara (Biosaintifika: Journal of Biology & Biology Education, 2018)
Daemonorops draco has been reported for its antibacterial activity and empirically used for wound healing by Anak Dalam ethnic at Jambi Province, Sumatera-Indonesia. This study was performed to evaluate antibacterial and antibiofilm activity of D. draco resin collected from Jambi. D. draco resin was extracted using n-hexane, ethyl acetate and methanol, respectively. Antibacterial activity of the extracts was evaluated using agar diffusion method against Staphylococcus aureus and Eschericia coli, whereas the minimum inhibitory concentration (MIC) and minimum bacteriacidal concentration (MBC) was determined by microdilution method. In addition, antibiofilm activity was evaluated by violet crystal method. The result showed that extraction yield of ethyl acetate was higher than methanol and n-hexane. Ethyl acetate and methanol extracts of D. draco exhibited stronger antimicrobial activity against S. aureus compare to n-hexane extract. MIC and MBC of methanol extract and chromatographic fraction (F5.1) of ethyl acetate extract were 0.5 and 1.0 mg/mL, respectively. In addition, antibiofilm assay revealed that all extracts were inhibit initial attachment of bacteria cell in biofilm formation. This result revealed a novel information that Â D. draco extracts was potential as inhibitor of biofilm formation. TLC bioautography of D. draco extracts indicated that constituent with Rf of 0.71 performed antimicrobial activity against S. aureus. This finding expected to strengthen the scientific backup for utilization of D. draco by society.